Safety in numbers : problems of a smaller U.S. nuclear arsenal in Asia - Christine M. Leah (2014)
This paper argues that the Asia Pacific region is not ready for further nuclear reductions by the United States. After the end of the Cold War, the United States was able was reduce its nuclear and conventional forces and take an intellectual “holiday” from the demands of END against the Soviet Union. However, that has been changing over the last few years. Nuclear weapons are becoming more central to interstate relations as the centre of global strategic gravity shifts increasingly to the Asia Pacific. With the expansion of Chinese military power and greater uncertainty over its strategic and military ambitions,1 nuclear weapons remain a relevant instrument in helping to manage proliferation and great power strategic relations. As such, it is not at all clear that a smaller U.S. nuclear force will contribute to greater stability in the Asia Pacific. This paper provides arguments against reductions in the size of the U.S. nuclear arsenal below 1,000 warheads by examining both the effects this will have on allies, and the inherent strategic complications that will arise. In short: Will a reduction in nuclear weapons lead to a more stable Asia? The answer is probably no. To support this claim, I advance the following four claims. First, nuclear weapons are uniquely stabilising instruments of deterrence. Second, that extended nuclear deterrence has always been central to Washington’s alliances. Sometimes this phenomenon has been implicit, at other times it has been explicit. Third, given the geopolitical transformations underway in the Asia Pacific, further nuclear reductions undermine flexibility of response and the concept of escalation control across both the nuclear and conventional realms of warfare. Lastly, that as a consequence, Asia Pacific allies may increasingly doubt the seriousness of Washington’s assurances. If extended nuclear deterrence does not have a future, then serious options come back onto the agenda for those allies.